1994
DOI: 10.1016/0266-7681(94)90171-6
|View full text |Cite
|
Sign up to set email alerts
|

Wrist Arthrodesis Using a Sliding Radial Graft and Plate Fixation

Abstract: In a retrospective study, the results of 18 wrist fusions with a radial sliding graft and a dynamic compression plate are reviewed. All 18 fusions united, with an average position of 16 degrees of extension and 7 degrees of ulnar deviation. Wrist strength and stability and diminished pain allowed improved function. However, decreased maneuverability impaired function for some activities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 21 publications
1
13
0
Order By: Relevance
“…The use of iliac crest bone graft is controversial. Sorial et al (1994) used only a local bone sliding radial graft and Weiss and Hastings (1995) used local radial metaphyseal bone graft harvested from below the plate. Hartigan et al (2001) used proximal carpal bone graft, performing a proximal row carpectomy at the time of fusion.…”
Section: Discussionmentioning
confidence: 99%
“…The use of iliac crest bone graft is controversial. Sorial et al (1994) used only a local bone sliding radial graft and Weiss and Hastings (1995) used local radial metaphyseal bone graft harvested from below the plate. Hartigan et al (2001) used proximal carpal bone graft, performing a proximal row carpectomy at the time of fusion.…”
Section: Discussionmentioning
confidence: 99%
“…11-14,36,48 -50 Mackenzie,12 in 1960, reported on the indication of wrist arthrodesis in brachial plexus palsy and performed it in 17 patients, improving both function and appearance of the upper extremity, using bone graft from the distal ulna. Authors such as Sorial et al, 36 Monreal, 49 Bentolila et al, 50 Takka et al, 52 Brunelli et al, 53 Anderson and Thomas, 54 and others have documented the use of wrist stabilization in patients with upper extremity deficit. Addosooki et al 10 showed their technique for wrist fusion in 18 patients, placing the rigid plate between the radius and the second metacarpal.…”
Section: Discussionmentioning
confidence: 96%
“…The AO plate provides instant stability, with only 4 weeks of volar splinting necessary and early finger mobilization preventing joints contractures. 16,27,36,38 The fusion was augmented with the use of bone grafting. There is a tendency in patients with long denervation time to have osteoporosis; in these patients, the use of the iliac crest corticocancellous graft is preferred because the cancellous part helps to consolidate the carpus and the cortical part gives stability.…”
Section: Plastic and Reconstructive Surgery • December 2009mentioning
confidence: 99%
“…Sorial et al reported successful fusion in 18 patients with the use of a radial sliding graft fixed with a dynamic compression plate 5 . There are many studies in literature of wrist arthrodesis in painful wrist with synthes fusion plate 6,7 but due to poor patient affordibilty we used 3.5 mm reconstruction plate.…”
Section: Ray 3 Months Lateral Viewmentioning
confidence: 99%